UNIQLO x Manga & Anime: Cultural Globalization and Community Acceptance in Indonesia - Novi Amalia Putri; Hamdan Nafiatur Rosyida; Havidz Ageng Prakoso (Priviet Social Sciences Journal, 2025)
This research aims to examine the role of UNIQLO's collaboration with manga and anime in the globalization of Japanese culture and the global community's acceptance of products with a Japanese cultural identity. This study uses a qualitative method with an in-depth interview approach with 51 respondents involved in the consumption of manga- and anime-themed UNIQLO products. The data obtained were analyzed using NVivo software to identify the main themes in the public acceptance of the product. In addition to the interviews, this research is also supported by a literature review of various studies. The results show that the majority of respondents agree that manga and anime play an important role in people's acceptance of Japanese culture, especially through UNIQLO's collaboration, which integrates popular characters in their product designs. This collaboration not only increases interest in the product, but also introduces broader elements of Japanese culture into consumers' daily lives.